Intensity of income diversification among small-holder farmers in Asayita Woreda, Afar Region, Ethiopia - Mohammed Adem; Fentahun Tesafa (Cogent Economics & Finance, 2020)
This paper examines measuring the intensity of income diversification and identifying the factors which determine level of income diversification in Asayita woreda Eastern part of Afar region. The study used multi stage sampling in combination with stratified and simple random sampling procedures to select kebeles and households. The Simpson Index of Diversity (SID) and Fractional response model were employed to analyse the data collected from a sample of 153 rural households. The level and type of income diversification depends on the accessibility and availability of different income sources. The mean results of degree of income diversification revealed that Simpson Index of Diversity (SID = 0.24) by rural households in the study area. Based on fractional response model educational status, credit utilization, distance from market and access to electric power affect at p < 0.01% probability level, sex of the household head affect at p < 0.05% probability level and, annual household income, special skill and household size significantly affecting degree of income diversification at p < 0.1% probability level. The finding of this research indicates important policy implications suggesting that programs, projects and/or any interventions designed targeting to engage people in other income-generating activities would augment their income sources, which are made to increase the level of income diversification at household level in Asayita woreda.
Keywords: 330; income diversification; fractional response regression; income; Simpson Index of Diversity